2017
DOI: 10.1017/gmh.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

Implementing mhGAP training to strengthen existing services for an internally displaced population in Pakistan

Abstract: Background.In 2014, over a million people were internally displaced after the launch of a military operation in North Waziristan, a tribal region on Pakistan's side of the Durand Line. Despite security concerns and restrictions, a collaborative mental health and psychosocial support initiative was undertaken in the district of Bannu. Monthly mental health camps were conducted for a period of 6 months by a multidisciplinary mental health team. The initiative also helped to assess mental health needs and plan tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
55
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 20 publications
0
55
0
Order By: Relevance
“…The adapted version consisted of 6 true/false and 9 multiple choice questions. The pre-and post-knowledge questionnaire has been used to evaluate a number of mhGAP interventions [24][25][26][27][28].…”
Section: Programme Evaluation Knowledge Confidence and Attitudesmentioning
confidence: 99%
“…The adapted version consisted of 6 true/false and 9 multiple choice questions. The pre-and post-knowledge questionnaire has been used to evaluate a number of mhGAP interventions [24][25][26][27][28].…”
Section: Programme Evaluation Knowledge Confidence and Attitudesmentioning
confidence: 99%
“…As noted above, while the mhGAP package does include a set of freely available training videos, participants in the Siriwardhana et al study concluded that provision of videos in the local Tamil language would be more appropriate and effective. Other researchers have also found that videos included in the mhGAP package were not necessarily suitable due to issues of language and culture, and instead role-play was prioritised to enhance the learning process [14].…”
Section: Introductionmentioning
confidence: 99%
“…Training in the first version of mhGAP-IG demonstrated improvements in pre-and post-training knowledge testing, but with the need for ongoing supervision 3,4 . Feedback collected by the WHO requested more experiential learning; a focus on building skills; easier access to training materials; shorter training of six days maximum with post-training supervision, and the addition of clinician competencies.…”
mentioning
confidence: 99%
“…These lack the formality and resource-intensiveness of observed structured clinical examinations, which have high reliability and validity in clinical skill assessment 8 , but share similarities, such as instructions on discrete clinical scenarios, timing, checklists for candidate demonstration, and capacity for multiple role-plays to improve reliability and cover various skills. Role-plays also have the advantage of established acceptability in LMIC training settings 3,4 , and can utilize peer assessment to manage limited assessor availability 8 .…”
mentioning
confidence: 99%